2014
DOI: 10.1007/s11606-013-2754-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospitalist Discontinuity on Hospital Cost, Readmissions, and Patient Satisfaction

Abstract: BACKGROUND: Achieving patient-physician continuity is difficult in the inpatient setting, where care must be provided continuously. Little is known about the impact of hospital physician discontinuity on outcomes. OBJECTIVE: To determine the association between hospital physician continuity and percentage change in median cost of hospitalization, 30-day readmission, and patient satisfaction with physician communication. DESIGN: Retrospective observational study using various multivariable models to adjust for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…transitions in care) that cannot be experienced by those with shorter stays. 6,7 Because physician discontinuity and physician communication has previously been shown to negatively impact patient satisfaction, patients with prolonged hospital stays are the best barometers of how these challenges are being met in the inpatient setting. The impact of hospital structural variables, such as continuity of care, on patient satisfaction is best studied by examining the patients who are most impacted by transitions in care.…”
Section: Introductionmentioning
confidence: 99%
“…transitions in care) that cannot be experienced by those with shorter stays. 6,7 Because physician discontinuity and physician communication has previously been shown to negatively impact patient satisfaction, patients with prolonged hospital stays are the best barometers of how these challenges are being met in the inpatient setting. The impact of hospital structural variables, such as continuity of care, on patient satisfaction is best studied by examining the patients who are most impacted by transitions in care.…”
Section: Introductionmentioning
confidence: 99%
“…Key clinical information may be lost during physician‐to‐physician handoffs (eg, at admission, at the end of rotations on service) during hospitalization. Our research group recently found that lower hospital physician continuity was associated with modestly increased hospital costs, but also a trend toward lower readmissions . We speculated that physicians newly taking over patient care from colleagues reassess diagnoses and treatment plans.…”
mentioning
confidence: 98%
“…We sought to examine the relationship between hospital physician continuity and the incidence of adverse events (AEs). We combined data from 2 previously published studies by our research group; one investigated the relationship between hospital physician continuity and costs and 30‐day readmissions, the other assessed the impact of unit‐based interventions on AEs …”
mentioning
confidence: 99%
“…1 Discontinuity was measured by modifying two tools that are typically applied in the outpatient rather than inpatient setting: the Usual Provider of Care Index (UPC) 2 and the Number of Physicians Index (NPI). 3 The authors found that discontinuity was associated with increased costs, had no impact on patient satisfaction and trended toward fewer readmissions.…”
mentioning
confidence: 99%